Government’s impression management strategies, trust in government and social cohesion: An evidence from Songjiang University Town, China - Fan, Juan; Liang, Wenhui; Zheng, Hanyi (Frontiers in Psychology, 2022)
Trust in government and social cohesion are crucial guarantees for long-term social stability. With the development of the Internet, cross-border flows of information have become increasingly easier, enabling more factors to influence people’s political perceptions and loyalty. This study explores the mechanism of governments’ impression management behaviors on trust in government and social cohesion using the questionnaire survey with college students in Shanghai as the research subjects. Impression management strategies are classified into promotive ones and protective ones herein based on the social psychology theory. The results indicate that both promotive and protective impression management strategies take by governments positively affect citizens’ loyalty, and loyalty positively affects citizens’ social cohesion and the level of trust in government; moreover, the level of trust in government positively affects social cohesion. These findings provide implications for boosting the sound development of China’s political society during the transition period.